RIGHT TO USE OF MILITARY DORMITORY FOR PERSONAL BUSINESS ACCORDING TO MILK AD-DAULAH THEORY - Nabila Merriza; Ida Friatna; Syukri (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This article aims to examine the management system and use of the TNI Dormitory for personal business at the Kuta Alam Dormitory in Banda Aceh based on the concept of milk al-daulah. The approach the author uses is juridical-empirical research. The results of the research show that the management of state-owned official residences is strictly regulated in Government Regulation Number 40 of 1994 and amendments through Government Regulation Number 31 of 2005, which limits their use to state officials, civil servants and workers who work in government agencies as long as they are still active. active. Use of a country house for personal or commercial purposes without valid permission may be unlawful. However, businesses run by families of TNI soldiers with permission from the Head of the Dormitory and approval from the Military Command are considered legal, as long as they do not change the physical shape of the dormitory and do not interfere with TNI duties. From an Islamic legal perspective, TNI dormitories are milk al-daulah or state property which must be managed for the public benefit and must not be misused for personal gain. The use of TNI dormitories for private businesses managed by the families of TNI soldiers can provide positive benefits for the surrounding community, but must always comply with applicable legal provisions so as not to violate the principles of fair management of state property and milk al-daulah. This research provides an understanding of the importance of managing state assets in accordance with positive law and Islamic legal principles to achieve the public benefit.